2020
DOI: 10.1088/1757-899x/913/4/042071
|View full text |Cite
|
Sign up to set email alerts
|

“Green” technologies in housing: the experience of Russia

Abstract: In modern economic conditions, the environmental factors, including the housing construction, are becoming increasingly important. There is no universal model of economic development in the world that does not disturb the balance of economic, social and environmental interests. Nevertheless, scientists from many countries are working in this direction, realizing the scale of the serious negative consequences of the existing economic development model functioning. The development of housing on the basis of inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The new hardware and software complex must be able to independently recognize passengers' deviant behavior both inside the trains and on the platforms basing on the video flow from the cameras. In June 2021 two brand "Lastochks" trains were equipped in accordance with the third automation level (GoA3) as part of a pilot project (and underwent about 2 thousand tests under different weather conditions), [4]which implies automatic train movement and halt, though human involvement is required to open and close the doors and provide security in emergency situations.…”
Section: Methodsmentioning
confidence: 99%
“…The new hardware and software complex must be able to independently recognize passengers' deviant behavior both inside the trains and on the platforms basing on the video flow from the cameras. In June 2021 two brand "Lastochks" trains were equipped in accordance with the third automation level (GoA3) as part of a pilot project (and underwent about 2 thousand tests under different weather conditions), [4]which implies automatic train movement and halt, though human involvement is required to open and close the doors and provide security in emergency situations.…”
Section: Methodsmentioning
confidence: 99%
“…A hedge of brilliant dogwood (Cotoneaster lucidus Schlecht.) along the path visually separates the playground from the volleyball court, which is located on the adjacent plot [7]. The sports and recreation area is located in the south-east of the territory.…”
Section: Analysis Of the Main Ers Data Sources For The Dem Developmentmentioning
confidence: 99%
“…Porfiryev (2018) expressed another opinion about the need to develop green technologies in Russia. Bachurinskaya et al (2020) demonstrated the use of green technologies in the private sector and their insufficient efficiency in Russia; Kapitonov et al (2016) analyzed the development of green energy in several regions of Russia, however did not provide a comprehensive analysis. Vashchuk and Titov (2016) focused only on clustering without taking into account foreign experience for Russia.…”
Section: Introductionmentioning
confidence: 99%